THE EFFECT OF ADDITION OF SUGAR CANE JUICE AND TURMERIC ON THE PHYSIOCHYMIC AND ORGANOLEPTIC PROPERTIES OF HERBAL YOGHURT - Nafisa, Daratina; Minah, Faidliyah Nilna (jurnal ATMOSPHERE, 2026)
Yogurt is a fermented product of cow's milk by lactic acid bacteria that has a sour taste. Making yogurt requires innovation, namely the addition of herbal ingredients such as turmeric as a natural dye and sugarcane juice as a natural sweetener. The method used in this study was the fermentation of lactic acid bacteria Lactobacillus bulgaricus and Streptococcus thermopillus. The variables used were the addition of turmeric (0.2gr, 0.4gr, and 0.6gr) and the addition of sugarcane juice (4ml, 8ml, 12ml, 16ml, and 20ml). The analysis used was pH, viscosity, lactic acid level test, density test, and organoleptic test. In the pH test, the results obtained ranged from 3.8-4.5, the lactic acid content test ranged from 0.81-0.98% b/b, the density test ranged from 1.046-1.079 g/ml, the viscosity test ranged from 14.64-53.96 cp, and the organoleptic test showed the level of preference for yoghurt with the addition of 0.2 grams of turmeric and 12 ml of sugarcane juice. Based on the results obtained, the proportion of the addition of sugarcane juice and turmeric affects the quality of yoghurt.